Analisis Tingkat Kesejahteraan Pembudidaya Ikan Dalam Keramba Ikan Patin (pangasius sp) dan Ikan Toman (channa micropeltes) Di Kampung Kelumpang Kecamatan Mook Manaar Bulatn Kabupaten Kutai Barat - Jemly -; Juliani; Said Abdusysyahid (Jurnal Pembangunan Perikanan dan Agribisnis, 2024)
The purpose of the study was to determine the feasibility of fish farming in cages and the level of welfare of the farming community. This research was conducted in Kelumpang Village, West Kutai Regency. A total of 22 fish farmers were selected as respondents using a purposive sampling method. The method of analysis used an analysis of fish cultivators' business and exchange rates. The results of this study indicate that the average income obtained from fish farming in cages is Rs. 1.950.701.047,-/year. The welfare level of cultivators shows an NTPi value of 2.6 for household income of fish cultivators and an NTPi value of 0.65 for income from fishery products, which illustrates a very good level of cultivator welfare